Estado actual de la comercialización de productos artesanales a partir de especies maderables en los mercados del centro artesanal turístico Anaconda y San Juan Bautista, Loreto - 2022 - Chu Armas, Jose Luis (2022)
This study was carried out at the Anaconda Tourist Artisan Center at the Iquitos Artisans Association of the San Juan de Miraflores Peasant Community, Distric of San Juan, Province of Maynas, Loreto, in order to determine the current state of commercialization of artisanal products from timber species in the markets of the indicated artisanal centers. From the obtained results, it is found that the Anaconda and San Juan Craft Center in the city of Iquitos have a higher consumption of the Pali Sangre (52.38%) and Topa (28.57%) timber species, as well as the non-timber species Cambira (14.05%). The artisans of the San Juan Craft Center enjoy greater stability in their activity due to their seniority as a craft center, it has 17 years recognized by SUNAT but its seniority is greater. The modalities of acquisition of wood with the highest frequency are the purchase of wood and the purchase of clean handicrafts The greattest consumption of handicraft products is made by national tourism and in the second place by the international market, and it is necessary to improve the conditions for both markets. The artisans of the craft centers under study are located in socioeconomic categories D and E, these being the lowest on the scale with an average net income that does not exceed S/. 2500 /month.